Development of material for guidance on the use of growth hormone directed to children and their caregivers - Wiese, Januaria Ramos Pereira; Gonçalves, Graciele Schug; Pavesi, Leonilda Banki (Seven Editora, 2023)
Growth hormone (GH) deficiency is a syndrome caused by impaired GH secretion which may have congenital, less common, or acquired causes. To treat the deficiency, daily subcutaneous injections of GH are used. The treatment is effective and safe, but as it requires daily injections for many years, adherence can be affected. The pharmacist can provide guidance on the use of GH, identifying and solving problems that may compromise adherence to treatment. The objective of this work was to develop material to guide children using GH and their caregivers. In the first stage, interns and pharmacists exchanged their experiences about the consultations. Subsequently, there was a search for information in the literature about the main adherence problems found in the studies. Finally, we developed a Welcome Letter for the child and a Guidance Manual for caregivers. DOI:https://doi.org/10.56238/interdiinovationscrese-024